Analisis Kebutuhan Pengembangan Web Modul IPA Terintegrasi Tanaman Lokal untuk SMP - Puspa Indah Devitasari (STIE Syari'ah Al-Mujaddid Tanjung Jabung Timur, 2022)
This study aims to analyze the need for the development of an integrated science web module with local plants. This is motivated by the importance of real foundations such as the need for technology and learning content as well as opinions from teachers to develop media and learning resources. This research is a qualitative research with descriptive type. The data collection technique was done by interview, observation, and documentation. The results of the study indicate that the development of an integrated science web module with local plants is one of the solutions needed in dealing with science learning problems. Problems that can be overcome, such as learning using web modules, students will be more active in independent learning, student learning becomes more contextual with science integrated with local plants.